Customary Law and Sovereign Polity (Tlaxcala, South Africa, Basque Country) - Clavero, Bartolomé (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
In order to locate Basque foralism in a comparative setting, this essay proposes the consideration of a couple of cases: the singular case of historical foralism in the heart of present-day Mexico, namely in Tlaxcala, and the less peculiar case of community customary law within South Africa. The former mainly shows us that foralism can dilute in federalism. The second brings us face to face with the most important issue, not of mere legal tradition, but of the historical title to own law implying community self-rule. It is under the light of the prospects thus opened up and in the face of prevailing neglect that the case of Basque foralism in constitutional times is here addressed.